PENUAAN DINI DAN DURABILITAS PERKERASAN LAPIS TIPIS BETON ASPAL LAPIS AUS (HRS-WC) YANG MENGGUNAKAN ROADCEL-50 - Mashuri, Mashuri; Astuti, Fira; Batti, Joy Fredi (Jurusan Teknik Sipil Universitas Tadulako, 2014)
RoadCel-50 is an added material that has been used in asphalt pavement such as HRS. Its purpose is to improve the stability of the asphalt pavement. However, the effect of the use RoadCel-50 on short term aging and durability of asphalt pavement is very important to understand. The objective of this study was to determine the effect of RoadCel-50 on short term aging and durability of the pavement Hot Rolled Sheet Wearing Course (HRS-WC). This research was conducted with the percentage of the RoadCel-50 are 0%, 0.1%, 0.2%, 0.3% and 0.4%. This research was done at the Laboratory of Transportation and Highways Department of Civil Engineering Faculty of Engineering, Tadulako University, Palu Central Sulawesi. The main equipment used in this study is Marshall testing machines. Manufacturing and testing of samples were conducted at STOA conditions. The results of this study on the the condition of short term aging (STOA) shows that the use of RoadCel-50 can increase the stability of the pavement on the the percentage RoadCel-50 of 0.30% and Asphalt content of 7.7% which is 2281.40 kg.Â Stability in the condition STOA declined in the percentage RoadCel-50 of 0.40% and Asphalt content of 7.5% at 1178.87 kg. Applying RoadCel-50 on the HRS-WC can improve durability on the percentage RoadCel-50: 0.10% with 7.5% bitumen content. Keywords: Roadcel-50, Short term aging, HRS-WC, STOA.